If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 4u = -1u + 6 Reorder the terms: -9 + 4u = 6 + -1u Solving -9 + 4u = 6 + -1u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add 'u' to each side of the equation. -9 + 4u + u = 6 + -1u + u Combine like terms: 4u + u = 5u -9 + 5u = 6 + -1u + u Combine like terms: -1u + u = 0 -9 + 5u = 6 + 0 -9 + 5u = 6 Add '9' to each side of the equation. -9 + 9 + 5u = 6 + 9 Combine like terms: -9 + 9 = 0 0 + 5u = 6 + 9 5u = 6 + 9 Combine like terms: 6 + 9 = 15 5u = 15 Divide each side by '5'. u = 3 Simplifying u = 3
| 15y^3-18y^2+3y= | | -4(3x-8)=2 | | -3-5s=-7-6s | | x+x(.15)=315000 | | -6y+2=4-6y | | f(x)=5x^2-6x+5 | | A=pir^2+2pirh | | X^4-40X^2-33=0 | | 4(3n+1)=6(2n-1) | | 9j=-7+10j | | 24.3=12.4+2a | | -3x-2+1=-7 | | -7g=-2-6g | | 12x^2-16x-6=0 | | -7g=-2-6 | | 12k=-36 | | 16-20x-21-6x=18-6x-12x-1 | | -5y+10=-6y | | 23a+7= | | 9v=10v+9 | | 17-6x+3x-5=x+11+4x | | -3m+10=-4m | | 17-6x+3x-5=x+11 | | 6+16x=17x+2 | | 5h=7h+8 | | 24.3=14.4+2a | | 18a-7= | | 6=-5d+11 | | 10x-14-6x=18 | | 2(2x+5)=4 | | 4z-4=10 | | 9x+16=6x+106 |